Changes in the rehabilitation status of irrigated lands in the Volgograd Oblast during 2001–2018 - I. N. Gorokhova; E. I. Pankova (Бюллетень Почвенного института им. В.В. Докучаева, 2022)
A comparative assessment of the rehabilitation status of irrigated lands, which are located in different natural areas of the Volgograd Oblast, is presented for 2001–2018. It was found that during the specified period there were recorded significant changes in the condition of irrigated lands: the total irrigation area has dramatically decreased since 2001 (-31%), especially at local runoff (-44.5%), the groundwater level has decreased (the level >5 m remains on 78% of the area). Also on this background, the areas of secondary salinized soils were also decreased (-3.9%). The main problems at the present are: the presence of fallow lands and rain-fed lands initially cultivated for irrigation, the lack of drainage on the most of irrigation systems and significant areas of saline soils requiring rehabilitation. Differences in natural conditions have largely determined the current rehabilitation state of irrigated soils and the intensity of their changes. Thus, the largest areas of secondary saline soils are preserved on irrigation systems located on the initially highly saline, poorly drained soils of the Khvalyn clay plain (Pallasovka, Svetloyarsk irrigation systems). Reconstruction of a number of irrigation systems with areas of secondary saline soils gave a positive result, after which secondary saline soils on reclaimed lands were not detected (Large Volgograd, Tyazhin irrigation systems). Significant areas of saline soils can be found on irrigated lands in the distribution areas of natural saline soils and chestnut, light chestnut saline soils – in the south of the Volga Upland, in the area of the Northern Yergeni and on the Khvalyn clay plain (Gorodishуsche, Generalovskoye, Pallasovka, etc. irrigation systems). Inherent research on the Volga-Don irrigation system with the involvement of remote sensing data has shown that this system reflects the general features of the modern rehabilitation condition of irrigated lands of the Volgograd Oblast – fallow lands, lack of drainage, and widespread saline soils are specific for this area. The use of high-resolution multispectral satellite images (Landsat-8, Sentinel-2) for the purposes of detection of fallow and irrigated lands in the current season demonstrates the possibility of clarifying information on this category of land. The determination of the distribution of salinized and solonetzic soils on irrigated lands of the Volgograd Oblast by remote methods can be carried out indirectly, i. e. according to the state of vegetation: when areas of sparse vegetation cover are being identified on images, targeted routes for soil surveys and soil sampling are selected.